Socio-economic characteristics of parents on learners’ educational aspiration: Exploring mechanisms of impact - Zang, Paulina Lamisi; Kwao, Moses Paafio; Anim, Christian Lawerh; Ahasu, Emmanuel Kwame (American Journal of Education and Learning, 2024)
This study aims to examine the influence of the socio-economic status (SES) of parents on learners’ educational aspirations in La Dade Kotopon of the Greater Accra region of Ghana. Socio-economic status of parents plays a pivotal role in shaping their child’s educational aspirations and the pathways they envision for their future. Socio-economic status is a multidimensional construct encompassing various factors such as parental education, occupation, income, and family background. The study utilizes a quantitative research design, employing a sample of learners (230) from diverse socio-economic backgrounds within the Greater Accra region through the quota sampling technique. Also, the convenient sampling technique was used in selecting ten (10) teachers and thirty (30) parents. The data were collected using a questionnaire and analysed using descriptive statistics like frequencies, percentages, mean, and SD. It was found that most of the guardians of La Dade Kotopon Junior High School (JHS) were not employed, while a majority were into petty trading. Therefore, the income level of the guardians was low, placing most of them in low socio-economic backgrounds. This had affected the learners in terms of their choice of schools and their educational aspirations. Practical implications arise in designing targeted interventions and support programs aimed at fostering educational aspirations, especially for learners from disadvantaged socio-economic backgrounds.